Intra-abdominal septic complications after ileocolic resection increases risk for endoscopic and surgical postoperative Crohn's disease recurrence. (15th June 2022) - Bachour, Salam P; Shah, Ravi S; Rieder, Florian; Qazi, Taha; Achkar, Jean Paul; Philpott, Jessica; Lashner, Bret; Holubar, Stefan D; Lightner, Amy L; Barnes, Edward L; Axelrad, Jordan; Regueiro, Miguel; et al.
Abstract: Background: Postoperative recurrence [POR] of Crohn's disease following ileocolonic resection is common. The impact of immediate postoperative intra-abdominal septic complications [IASC] on endoscopic and surgical recurrence has not been elucidated. Aims: To evaluate if IASC is associated with an increased risk for endoscopic and surgical POR. Methods: This was a retrospective study of adult Crohn's disease patients undergoing ileocolonic resection with primary anastomosis between 2009 and 2020. IASC was defined as anastomotic leak or intra-abdominal abscess within 90 days of the date of surgery. Multivariable logistic and Cox proportional hazard modelling were performed to assess the impact of IASC on endoscopic POR [modified Rutgeerts' score ≥ i2b] at index postoperative ileocolonoscopy and long-term surgical recurrence. Results: In 535 Crohn's disease patients [median age 35 years, 22.1% active smokers, 35.7% one or more prior resection] had an ileocolonic resection with primary anastomosis. A minority of patients [ N  = 47; 8.8%] developed postoperative IASC. In total, 422 [78.9%] patients had one or more postoperative ileocolonoscopies, of whom 163 [38.6%] developed endoscopic POR. After adjusting for other risk factors for postoperative recurrence, postoperative IASC was associated with significantly greater odds (adjusted odds ratio [aOR]: 2.45 [1.23–4.97]; p  = 0.01) and decreased time (adjusted hazards ratio [aHR]: 1.60 [1.04–2.45]; p  = 0.03] to endoscopic POR. Furthermore, IASC was associated with increased risk (aOR: 2.3 [1.04–4.87] p  = 0.03) and decreased survival-free time [aHR: 2.53 [1.31–4.87]; p  = 0.006] for surgical recurrence. Conclusion: IASC is associated with an increased risk for endoscopic and surgical POR of Crohn's disease. Preoperative optimization to prevent IASC, in addition to postoperative biological prophylaxis, may help reduce the risk for endoscopic and surgical POR. Graphical Abstract: